Literature Review on The Role of The Financial Services Authority (OJK) in Oversighting Sharia Investment - Wardani, Vanesa Putri; Basri, Muhammad Muinudinillah (Universitas Muhammadiyah Surakarta, 2020)
In overseeing investment, OJK collaborates with the Satgas Waspada Investasi (SWI). To oversee investments based on sharia principles, the OJK is assisted by the Dewan Pengawas Syariah (DPS) and the Majelis Ulama Indonesia (MUI). This review aims to determine the role of the Financial Services Authority in overseeing Islamic investment and assisting the public in choosing safe and licensed Islamic investments from the OJK. This type of research uses qualitative research with content analysis techniques. The results of this research show that OJK has not been optimal in preventive action because there are still many who are deceived by fraudulent investment, and the low level of financial literacy and inclusion in Indonesian society, while repressive action, OJK is quite maximal because it is firm in closing down investment companies that have the potential to be fraudulent and detrimental.